ASPHALT CONCRETE – WEARING COURSE (AC-WC) WITH CRUMB RUBBER MIXTURE PERFORMANCE EVALUATION - Syahputra, Deka; Subagio, Bambang Sugeng; Hariyadi, Eri Susanto (Jurnal Teknik Sipil, 2019)
AbstractThis study aims to measure the performance of a mixture of Asphalt Concrete - Wearing Course (AC-WC) with addition of crumb rubber using a dry process, where crumb rubber as an aggregate replacement of fraction no. 50 with mixture variations of 0%, 25%, and 50%. The method used in this research is the experimental method in the laboratory. Primary data collection is done through testing of aggregates, asphalt, crumb rubber, and mixtures. Hot mix design used Marshall test to obtain Optimum Bitumen Content (OBC). Laboratory test in OBC conditions obtain consist of Resilient Modulus test used Dynamic Testing System (DTS) at 25°C, 35°C, and 45°C and rut depth test used Hamburg Wheel Tracking (HWT) at temperatures 45°C and 60°C. The results of addition of crumb rubber content to the mixture can increase the value of OBC and reduce the value of Marshall stability, the percentage of 50% crumb rubber obtained highest OBC and the lowest Marshall stability. The crumb rubber content in the mixture lowers the value of Modulus Resilient, AC-WC with 0% crumb rubber has the highest value. At a temperature of 60°C, 25% crumb rubber content in the mixture reduces the rut depth value. Based on the Marshall stability, Resilient Modulus, and rut depth values, then the crumb rubber content to replace aggregate fraction no. 50 in the AC-WC gives the highest value is 25% in laboratory test. AbstrakPenelitian ini bertujuan untuk mengukur kinerja campuran laston lapis aus (AC-WC) yang dimodifikasi dengan serbuk ban bekas (crumb rubber) menggunakan proses kering, dimana crumb rubber sebagai subtitusi agregat fraksi no. 50 dengan variasi campuran 0%, 25%, dan 50%. Metode yang digunakan dalam penelitian ini adalah metode eksperimen di laboratorium. Pengumpulan data primer dilakukan melalui pengujian terhadap agregat, aspal, crumb rubber, dan campuran. Perencanaan campuran beraspal panas menggunakan metode Marshall untuk mendapatkan Kadar Aspal Optimum (KAO). Pengujian laboratorium pada kondisi KAO yang didapat terdiri atas pengujian Modulus Resilien dengan menggunakan alat Dynamic Testing System (DTS) pada temperatur 25°C, 35°C, dan 45°C serta pengujian rut depth dengan menggunakan alat Hamburg Wheel Tracking (HWT) pada temperatur 45°C dan 60°C. Dari hasil pengujian penambahan crumb rubber pada campuran dapat meningkatkan nilai KAO dan menurunkan nilai stabilitas Marshall, dimana pada persentase 50% crumb rubber didapat KAO tertinggi dan stabilitas Marshall terendah. Penambahan crumb rubber dalam campuran menurunkan nilai Modulus Resilien, dimana campuran AC-WC dengan 0% crumb rubber memiliki nilai yang paling tinggi. Selain itu, pada temperatur 60°C penambahan 25% crumb rubber dalam campuran memperkecil nilai rut depth. Berdasarkan nilai stabilitas Marshall, Modulus Resilien, dan rut depth tersebut maka kadar crumb rubber untuk pengganti agregat fraksi no. 50 yang memberikan nilai terbaik pada campuran AC-WC adalah 25% sesuai dengan pengujian di laboratorium.